2020
DOI: 10.1007/s12015-020-10067-w
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Administration of hNSCs Improves Neurological Recovery after Cardiac Arrest in Rats

Abstract: Irreversible brain injury and neurological dysfunction induced by cardiac arrest (CA) have long been a clinical challenge due to lack of effective therapeutic interventions to reverse neuronal loss and prevent secondary reperfusion injury. The neuronal regenerative potential of neural stem cells (NSCs) provides a possible solution to this clinical deficit. We investigated the neuronal recovery potential of human neural stem cells (hNSCs) via intracerebroventricular (ICV) xenotransplantation after CA in rats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Mechanistically, these behavioral improvements were achieved, at least in part, due to the replacement of injured neuronal cells by differentiation of the engrafted cells into neuronal cells with mature functions that facilitate brain recovery. [ 7a ] These findings, where MGE‐modified NSCs have a beneficial effect on neuronal recovery in rodents, suggest that a similar approach could benefit stem cell therapy for brain injury in humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mechanistically, these behavioral improvements were achieved, at least in part, due to the replacement of injured neuronal cells by differentiation of the engrafted cells into neuronal cells with mature functions that facilitate brain recovery. [ 7a ] These findings, where MGE‐modified NSCs have a beneficial effect on neuronal recovery in rodents, suggest that a similar approach could benefit stem cell therapy for brain injury in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In the first, we demonstrated that transplanted NSCs can promote endogenous NSC proliferation and migration in the subventricular zone and enhance neuronal survival and neurological functional recovery of the injured brain after CA. [ 7a ] However, the clinical application of stem cell therapy for ischemic brain injury has been hampered by the limited neuronal differentiation and poor long‐term survival of transplanted stem cells. [ 18 ] To overcome these difficulties, we turned to MGE, a strategy using non‐natural monosaccharide analogs that we reasoned could overcome difficulties in efforts to use transplanted NSCs to treat brain injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common approaches for the treatment of CNS diseases include bypassing the BBB and increasing the permeability of the BBB. Methods of bypassing the BBB include intracerebroventricular [ 58 ], intracerebral [ 59 ], intrathecal [ 60 ], intranasal [ 61 ] and intratympanic [ 62 ] routes of administration, by which route the drug is delivered to the brain through the sense of smell and the trigeminal nerve [ 63 ]. Modification with antibodies or ligands of high expression on brain endothelial cells can increase the permeability of the BBB [ 64 ], and the combined application of CPP is also used to improve delivery efficiency [ 8 ].…”
Section: The Dilemma Of Treatment Of Cnsmentioning
confidence: 99%